Cholinergic stimulation with pyridostigmine improves autonomic function in infarcted rats. (23rd August 2013) - de La Fuente, Raquel N; Rodrigues, Bruno; Moraes‐Silva, Ivana C; Souza, Leandro E; Sirvente, Raquel; Mostarda, Cristiano; De Angelis, Kátia; Soares, Pedro P; Lacchini, Silvia; Consolim‐Colombo, Fernanda; Irigoyen, Maria‐Cláudia
Summary: In the present study we evaluated the effects of short‐term pyridostigmine bromide (0.14 mg/mL) treatment started early after myocardial infarction (MI) on left ventricular (LV) and autonomic functions in rats. Male Wistar rats were divided into control, pyridostigmine, infarcted and infarcted + pyridostigmine‐treated groups. Pyridostigmine was administered in the drinking water, starting immediately after MI or sham operation, for 11 days. Left ventricular function was evaluated indirectly by echocardiography and directly by LV catheterization. Cardiovascular autonomic control was evaluated by baroreflex sensitivity (BRS), heart rate variability (HRV) and pharmacological blockade. All evaluations started after 7 days pyridostigmine treatment and were finalized after 11 days treatment. Pyridostigmine prevented the impairment of +dP/dT and reduced the MI area in infarcted + pyridostigmine compared with infarcted rats (7 ± 3% vs 17 ± 4%, respectively). Mean blood pressure was restored in infarcted + pyridostigmine compared with infarcted rats (103 ± 3 vs 94 ± 3 mmHg, respectively). In addition, compared with the infarcted group, pyridostigmine improved BRS, as evaluated by tachycardic (1.6 ± 0.2 vs 2.5 ± 0.2 b.p.m./mmHg, respectively) and bradycardic (−0.42 ± 0.01 vs −1.9 ± 0.1 b.p.m./mmHg) responses, and reduced the low frequency/high frequency ratio of HRV (0.81 ± 0.11 vs 0.24 ± 0.14, respectively). These improvements are probably associated with increased vagal tone and reduced sympathetic tone in infarcted + pyridostigmine compared with infarcted rats. In conclusion, the data suggest that short‐term pyridostigmine treatment started early after MI can improve BRS, HRV and parasympathetic and sympathetic tone in experimental rats. These data may have potential clinical implications because autonomic markers have prognostic significance after MI.